The Role of MycoSilvi, Lime and Compost on The Growth of Balsa (Ochroma bicolor Rowlee.) Seedling in Post Silica Sand Mine Media - Andi Sukendro; Wilarso, Sri; Putri Maharani; Cahyo Wibowo (Journal of Sylva Indonesiana, 2020)
Problems arising from silica sand mining are decreasing soil fertility, as well as the presence of high heavy metals such as Fe and Al, which inhibits the growth of revegetation plants. The purpose of this study was to analyze the response of the growth of balsa seedlings (Ochroma bicolor Rowlee.) on silica sand post-mining media treated with MycoSilvi, compost, and lime and determine the most optimal combination of MycoSilvi, compost, and lime treatment. This study uses a completely randomized design (CRD) with a split-plot design with 3 treatment factors, namely the addition of MycoSilvi, compost, and lime. Each treatment consisted of five replications. The results showed that the planting media that were not treated (control) was not able to support the growth of balsa seedlings. The interaction of MycoSilvi, compost, and lime significantly affected the height, diameter, biomass, and percentage of mycorrhizal colonization parameters, and significantly affected the plant chlorophyll content. The combination of MycoSilvi type 1 treatment, namely Glomus mosseae and lime (C0K1M1) type, resulted in the highest total growth rate, diameter, biomass, and colonization percentage compared to other treatments. The addition of lime and compost to the growth medium can reduce the degree of mycorrhizal dependency of balsa seedling.